Cryopreservation of Tropical Plant Germplasm with Vegetative Propagation - Review of Sugarcane (Saccharum spp.) and Pineapple (Ananas comusus (L.) Merrill) Cases - Martinez-Montero, Marcos Edel; Arnao, Maria Teresa Gonzalez; Engelmann, Florent (IntechOpen, 2012)
None